Gasimova , Sabina - (:unkn) unknown (My University, 2026)
Sabina Uzeyir Gasimova graduated from the Faculty of English Language Teaching of Azerbaijan University of Foreign Languages in 1995. After working as an English language teacher in secondary education, she joined the Azerbaijan University of Architecture and Construction (AzUAC) in 2000. She has been a Senior Lecturer at the Department of Foreign Languages since 2010. Her research interests include English language teaching methodology, foreign language education, and applied linguistics. She is the author of three books, two course syllabi, and more than 20 scientific articles.